2019
DOI: 10.1155/2019/5305014
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Roles of Estrogen Receptor β in Renal Calcium Oxalate Crystal Formation via Reducing the Liver Oxalate Biosynthesis and Renal Oxidative Stress-Mediated Cell Injury

Abstract: Females develop kidney stones less frequently than males do. However, it is unclear if this gender difference is related to altered estrogen/estrogen receptor (ER) signaling. Here, we found that ER beta (ERβ) signals could suppress hepatic oxalate biosynthesis via transcriptional upregulation of the glyoxylate aminotransferase (AGT1) expression. Results from multiple in vitro renal cell lines also found that ERβ could function via suppressing the oxalate-induced injury through increasing the reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…NADPH oxidase is confirmed as the main source of free radicals in kidneys, Liang et al found that the activation of androgen receptor (AR) signaling contributed to the upregulation of NADPH oxidase, which increased oxalate biosynthesis and oxidative stress, inducing kidney tubular injury and promoting stone formation 35 . In another study, estrogen/estrogen receptor beta (ERβ) exerted protective effect on renal CaOx crystal formation by inhibiting liver oxalate biosynthesis and reducing the expression of NADPH oxidase subunit 2 (NOX2) 36 . Sun et al reported pretreatment with taurine markedly reduced oxidative stress by promoting SOD2 activity and decreasing MDA concentration, and also suppressed ROS-dependent autophagy through activating Akt/mTOR pathway, thus alleviating crystal-induced oxidative injury in kidney tissues and HK-2 cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase is confirmed as the main source of free radicals in kidneys, Liang et al found that the activation of androgen receptor (AR) signaling contributed to the upregulation of NADPH oxidase, which increased oxalate biosynthesis and oxidative stress, inducing kidney tubular injury and promoting stone formation 35 . In another study, estrogen/estrogen receptor beta (ERβ) exerted protective effect on renal CaOx crystal formation by inhibiting liver oxalate biosynthesis and reducing the expression of NADPH oxidase subunit 2 (NOX2) 36 . Sun et al reported pretreatment with taurine markedly reduced oxidative stress by promoting SOD2 activity and decreasing MDA concentration, and also suppressed ROS-dependent autophagy through activating Akt/mTOR pathway, thus alleviating crystal-induced oxidative injury in kidney tissues and HK-2 cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a high concentration of oxalate could lead to renal injury and contribute considerably to the deposition and progression of calcium oxalate crystals [ 3 ]. A large amount of evidence suggests that increased calcium oxalate crystal adherence to and aggregation in renal tubular cells are related to the overproduction of reactive oxygen species (ROS) [ 4 ]. ROS result in serious renal tissue injuries, such as lipid peroxidation of the cellular membranes, presumably through OS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies also indicated that renal CaOx crystal deposition could be significantly decreased by antioxidant treatment in vivo [7,27,28]. Many other studies found that ROS is a key factor in the formation of CaOx stones by regulating a variety of signaling pathways, including the NF-κB pathway [29][30][31][32]. And Liu et al also found that the interaction between H19 and miR-216b promotes ROS and renal tubular epithelial cell injury in the process of CaOx nephrocalcinosis by HMGB1/TLR4/NF-κB pathway [12].…”
Section: Discussionmentioning
confidence: 99%